From stress neurobiology to sustainable housing : advancing knowledge on health and wellbeing for the North - Bellavance, Marie-Andrée; Gallais, Sophie (Université Laval, 2023)
Mental health and wellbeing are the critical basis by which humans can flourish, fulfil their potential, and remain resilient in the face of stress and adversity. However, mental disorders are one of the leading causes of disability worldwide. In Arctic and Subarctic regions, these challenges are particularly pressing because of the rapid social and cultural changes and their impacts on the wellbeing of Indigenous populations. Improving our capacity for diagnosis and treatment in multiple populations is crucial and involves providing new understanding of biological roots and sex-based differences of mental health problems, new early-detection methods, and new environmental and biological mechanisms that can be targeted for intervention. Moreover, sociocultural and environmental factors influence mental health and need to be considered as determinants of health. Within this holistic understanding of mental wellness, access to housing plays a major role. Indeed, not only do northern communities lack housing stock, but what is available may be of lower quality. This chapter gathers a selection of Sentinel North research results from a broad range of disciplines that contribute to understand the effects of stress on mental health and the mechanisms underlying the resilience to stress, to develop new tools for a better understanding of the brain and an early diagnosis of mental disorders, and to encourage an ecosystem approach for mental health and prevent health issues through culturally adapted actions on determinants of health, like access to sustainable and culturally appropriate housing.